The efficacy of thuricin CD, tigecycline, vancomycin, teicoplanin, rifampicin and nitazoxanide, independently and in paired combinations against Clostridium difficile biofilms and planktonic cells. Issue 1 (December 2016) - Mathur, Harsh; Rea, Mary; Cotter, Paul; Hill, Colin; Ross, R.
Abstract Background Thuricin CD is a two-component antimicrobial, belonging to the recently designated sactibiotic subclass of bacteriocins. The aim of this study was to investigate the effects of thuricin CD, as well as the antibiotics, tigecycline, vancomycin, teicoplanin, rifampicin and nitazoxanide when used independently and when combined at low concentrations on the viability ofClostridium difficile 20291 R027, TL178 R002, Liv022 R106, DPC6350 and VPI10463 biofilms and planktonic cells. Results On the basis of XTT (2, 3-bis[2-methyloxy-4-nitro-5-sulphophenyl]-2H-tetrazolium-5-carboxanilide)-menadione biofilm viability assays, we found that thuricin CD was effective against biofilms of R027, Liv022 R106 and DPC6350 when used independently while nitazoxanide and rifampicin were also potent against biofilms of R027 and DPC6350, when applied on their own. Tigecycline was found to be effective against R027 and DPC6350 biofilms, whereas teicoplanin and vancomycin when used independently were only effective against DPC6350 biofilms. The efficacies of the antibiotics rifampicin, tigecycline, vancomycin and teicoplanin againstC. difficile 20291 R027 biofilms were significantly potentiated when combined with thuricin CD, indicating effective antimicrobial combinations with this sactibiotic against R027 biofilms. However, the potency of nitazoxanide against R027 biofilms was significantly diminished when combined with thuricin CD, indicating an ineffective combination with this sactibiotic against R027 biofilms. Paired combinations of thuricin CD along with these five antibiotics were effective at diminishing the viability of DPC6350 biofilms. However, such combinations were largely ineffective against biofilms of TL178 R002, Liv022 R106 and VPI10463. Conclusions To the best of our knowledge, this is the first study to highlight the activity of a sactibiotic bacteriocin against biofilms and the first to reveal the potency of the antibiotics tigecycline, teicoplanin and nitazoxanide againstC. difficile biofilms. On the basis of this study, it is apparent that different strains ofC. difficile possess varying abilities to form biofilms and that the sensitivities of these biofilms to different antimicrobials and antimicrobial combinations are strain-dependent. Since the formation of relatively strong biofilms by certainC. difficile strains may contribute to increased cases of antibiotic resistance and recurrence and relapse ofC. difficile infection, the findings presented in this study could provide alternative strategies to target this pathogen.